Perfil clínico–epidemiológico dos recém-nascidos de muito baixo peso ao nascer admitidos em um hospital de referência no Estado do Ceará. - Melo, Carla Nayane Medeiros de (2018)
Prematurity, despite technological advances, stands out as one of the great problems of public health due to the high rates of morbidity and mortality. Low birth weight is the main classifier of the neonate as newborns at risk, which can lead to problems in the development of children and possible comorbidities in adult life. The present study aims to trace the clinical-epidemiological profile of very low birth weight newborns admitted to a Reference Hospital in the State of Ceará. METHODS: This is a quantitative, cross-sectional, descriptive study with an analytical approach. The study sample was the records of very low birth weight newborns admitted to the Neonatal Intensive Care Unit of the Dr. Waldemar de Alcântara General Hospital, from January 1, 2015 to December 31, 2015. December 31, 2016. The data collection was done through a protocol containing maternal and neonatal variables. To verify the existence of association between the variables, the Chi-square or Fisher's Exact tests were used. The study was approved by the Ethics and Research Committee of the Federal University of Ceará / PROPESQ. 128 newborns were divided into two groups: 1) extreme low birth weight (n = 37) and 2) very low birth weight (n = 91). The neonatal variables that had a statistically significant association with low birth weight were: female gender (p = 0.001); APGAR less than seven in the 1st and 5th minutes (both with p <0.001); lower gestational age (p <0.001); surfactant use (p <0.001); blood transfusion (p <0.001); clinical outcome (p <0.001); RN comorbidities (p = 0.005) and days of hospitalization (p = 0.013). The statistically significant maternal variables were prenatal visits (p <0.001) and immunization (p = 0.021), mainly anti-tetanus.